High-compaction phosphate positive electrode material, preparation method thereof and lithium ion battery positive electrode

By setting a B-C composite cladding on the surface of the positive electrode material of the lithium iron phosphate battery, the problem of its lower compaction density is solved, and higher energy density and better cycling performance is achieved, which is suitable for electric vehicles and energy storage systems.

CN119447267APending Publication Date: 2025-02-14SHENZHEN DYNANONIC CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411723039.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The compaction density of lithium iron phosphate batteries is limited in their application in electric vehicles and energy storage systems.

Method used

A B-C composite clad layer is provided on the surface of the phosphate-based positive electrode material to reduce the surface tension of the particles by the action of flux boron, and an amorphous glass borate layer is generated to prevent the electrolyte from contacting directly with the positive electrode material and slowly release the capacity.

Benefits of technology

The compaction density of the phosphate-based positive electrode material is significantly improved, thereby improving the energy density of lithium batteries, improving circulation performance, and showing broad prospects in energy storage applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447267A_ABST
    Figure CN119447267A_ABST
Patent Text Reader

Abstract

The invention provides a high-compaction phosphate positive electrode material, a preparation method thereof and a lithium ion battery positive electrode, the phosphate positive electrode material comprises a phosphate core and a B-C composite coating layer coating the surface of the phosphate core, and the B-C composite coating layer comprises BC3, borate and amorphous carbon; the general formula of the borate is MxByOz, M comprises Li and / or Fe, x is 1-3, y is 1-4, and z is 3-7; the preparation method comprises the following steps: mixing a phosphate precursor material, a boron source and a carbon source, and sequentially carrying out ball milling and sintering to obtain the high-compaction phosphate positive electrode material. According to the invention, the boron source can be melted at a high temperature and is used as a fluxing agent to reduce the surface tension of particles, improve the morphology of the particles and improve the compaction density of the phosphate positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a high-density phosphate-based positive electrode material and a preparation method thereof, and a lithium ion battery positive electrode. Background Art

[0002] Lithium iron phosphate battery is a high-performance lithium-ion battery that uses lithium iron phosphate as the positive electrode material. It has the advantages of high safety, long life and good low-temperature performance. Therefore, it has gradually become the mainstream battery technology in the fields of electric vehicles, energy storage systems, etc.

[0003] The energy density of a battery reflects the amount of energy that can be stored per unit mass, which has a direct impact on battery life. Compaction density is one of the important factors that affect the difference in battery energy density. Compared with other lithium batteries, lithium iron phosphate has a lower compaction density, which seriously limits its development.

[0004] In order to improve the competitiveness of lithium iron phosphate positive electrode materials in the market, it is necessary to develop products with high compaction density. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a high-density phosphate-based positive electrode material, a preparation method thereof, and a lithium-ion battery positive electrode. By setting a BC composite coating layer on the surface of the phosphate-based positive electrode material, the surface of the phosphate-based positive electrode material is made smoother, thereby greatly improving the compaction density of the phosphate-based positive electrode material, thereby improving the energy density of the lithium battery.

[0006] To achieve this object, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a high-density phosphate-based cathode material, the phosphate-based cathode material comprising a phosphate-based core and a BC composite coating layer coated on the surface of the phosphate-based core, the BC composite coating layer comprising BC3, borate and amorphous carbon; the borate has a general formula of M x B y O z , wherein M includes Li and / or Fe, x is 1-3, y is 1-4, and z is 3-7.

[0008] The technical purpose of the present invention is to provide a high-density lithium iron phosphate positive electrode material with a phosphate core surface having a BC composite coating, so as to overcome the problem of low compaction density of lithium iron phosphate. B is used as a flux. When a solid solution is formed during the sintering process, the lattice is distorted and activated, thereby reducing the surface tension of the particles and improving the particle morphology; at the same time, it reacts with alkali metal oxides (residual alkali) to form an amorphous glass borate layer / film. Specifically, the general formula of the borate includes M x B y Oz , wherein M includes Li and / or Fe. The glass borate layer / membrane can prevent the electrolyte from directly contacting the positive electrode material. The membrane layer can also slowly release capacity, and has broad prospects in energy storage applications.

[0009] Specifically, x is 1 to 3, for example, it can be 1, 1.3, 1.5, 1.7, 1.9, 2.2, 2.4, 2.6, 2.8 or 3, but it is not limited to the listed values, and other values ​​not listed in the range are equally applicable. y is 1 to 4, for example, it can be 1, 1.4, 1.7, 2, 2.4, 2.7, 3, 3.4, 3.7 or 4, but it is not limited to the listed values, and other values ​​not listed in the range are equally applicable. z is 3 to 7, for example, it can be 3, 3.5, 3.9, 4.4, 4.8, 5.3, 5.7, 6.2, 6.6 or 7, but it is not limited to the listed values, and other values ​​not listed in the range are equally applicable.

[0010] Preferably, the borate comprises any one or a combination of at least two of Li2B4O7, Li3BO3, Fe3(BO3)4 or LiFeBO3, wherein typical but non-limiting combinations are a combination of Li2B4O7 and Li3BO3, a combination of LiFeBO3 and Li3BO3, a combination of Li2B4O7 and LiFeBO3, and a combination of Fe3(BO3)4 and Li3BO3.

[0011] Preferably, the phosphate-based core includes lithium iron phosphate and / or lithium iron manganese phosphate.

[0012] Preferably, the particle size D50 of the phosphate-based positive electrode material is 0.8 μm to 1.1 μm, for example, it can be 0.8 μm, 0.84 μm, 0.87 μm, 0.9 μm, 0.94 μm, 0.97 μm, 1 μm, 1.04 μm, 1.07 μm or 1.1 μm.

[0013] Preferably, the thickness of the BC composite coating layer is 4 nm to 7 nm, for example, it can be 4 nm, 4.2 nm, 4.3 nm, 4.4 nm, 4.5 nm, 4.6 nm, 4.8 nm, 5.0 nm, 5.2 nm, 5.3 nm, 5.5 nm, 5.8 nm, 6.0 nm, 6.5 nm, 6.8 nm or 7.0 nm.

[0014] In the present invention, the thickness of the BC composite coating layer is preferably within the above range, which can ensure the cycle performance and improve the conductivity of the material, while avoiding the situation where the BC composite coating layer is too thick and hinders the migration and diffusion of Li ions, affecting the capacity release of the material.

[0015] Preferably, the B content in the high-density phosphate-based positive electrode material is 500ppm to 2500ppm, for example, 500ppm, 720ppm, 940ppm, 1160ppm, 1380ppm, 1600ppm, 1830ppm, 2050ppm, 2270ppm or 2500ppm, etc. The B content within this range can ensure that it is mixed with carbon to form a coating layer after melting.

[0016] Preferably, the C content in the high-density phosphate-based positive electrode material is 1.2wt% to 1.7wt%, for example, it can be 1.2wt%, 1.25wt%, 1.3wt%, 1.35wt%, 1.4wt%, 1.45wt%, 1.5wt%, 1.55wt%, 1.6wt% or 1.7wt%, etc.

[0017] When the C content is within this range, a uniform conductive layer can be formed to improve the electronic conductivity of the material, while not being too thick to block the lithium ion transmission channel.

[0018] Preferably, the existence form of B in the high-density phosphate-based positive electrode material includes BO bonds and / or BC bonds.

[0019] The invention speculates that the principle is: B generates two substances on the surface, one is BC3, which changes the valence band structure of the carbon-based material and increases the state density near the Fermi level, thereby improving the electronic conductivity of LFP; the other is a general formula M x B y O z The borate, wherein M comprises Li and / or Fe, has the effect of slowly releasing capacity.

[0020] In a second aspect, the present invention provides a method for preparing the high-density phosphate-based positive electrode material according to the first aspect, the preparation method comprising the following steps:

[0021] A phosphate-based precursor material, a boron source and a carbon source are mixed, and ball milling and sintering are performed in sequence to obtain a high-density phosphate-based positive electrode material.

[0022] The present invention preferably uses a phosphate precursor material for BC composite coating, wherein the phosphate precursor material is a positive electrode material that has been calcined and formed, and in the above sintering step, the secondary growth of phosphate particles is only carried out while the BC composite coating is carried out. The advantage of this arrangement is that the boron source melts at high temperature and acts as a flux to reduce the surface tension of the particles and improve the particle morphology; at the same time, it reacts with alkali metal oxides (residual alkali) to form an amorphous glass borate layer / film, which prevents the electrolyte from directly contacting the positive electrode material. The film layer can also play a role in slowly releasing capacity, which is very promising in energy storage applications. In addition, the present invention uses two-stage sintering, that is, the phosphate precursor material is first calcined and formed, and then the surface B is quickly put into a high-temperature molten state, so that B and C can be effectively coated on the surface of the positive electrode material to achieve the purpose of regulating the morphology.

[0023] Preferably, the boron source comprises boron oxide and / or boric acid.

[0024] Preferably, the carbon source comprises any one of glucose, sucrose, citric acid, ethylenediaminetetraacetic acid, polyethylene glycol or graphene, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of glucose and sucrose, a combination of citric acid and sucrose, a combination of glucose and citric acid, a combination of ethylenediaminetetraacetic acid and sucrose, a combination of ethylenediaminetetraacetic acid and graphene, and a combination of ethylenediaminetetraacetic acid and polyethylene glycol.

[0025] Preferably, based on the total amount of raw materials for forming a high-density phosphate-based positive electrode material, the amount of boron source added is 500ppm to 2500ppm, for example, it can be 500ppm, 720ppm, 940ppm, 1160ppm, 1380ppm, 1600ppm, 1830ppm, 2050ppm, 2270ppm or 2500ppm.

[0026] The present invention preferably controls the amount of boron source added within the above range. When the amount of boron source added is too low, there is a problem of insufficient formation of a dense protective film and inability to improve the particle morphology. When the amount of boron source added is too high, there is a problem of damaging the capacity.

[0027] Preferably, based on the total amount of raw materials for forming a high-density phosphate-based positive electrode material, the added amount of the carbon source is 5wt% to 10wt%, for example, it can be 5wt%, 5.6wt%, 6.2wt%, 6.7wt%, 7.3wt%, 7.8wt%, 8.4wt%, 8.9wt%, 9.5wt% or 10wt%, etc.

[0028] Preferably, the rotation speed of the ball mill is 450 rpm to 470 rpm, for example, it can be 450 rpm, 455 rpm, 456 rpm, 460 rpm, 465 rpm, 468 rpm or 470 rpm.

[0029] Preferably, the ball milling time is 4 h to 6 h, for example, it can be 4 h, 4.1 h, 4.2 h, 4.5 h, 4.8 h, 5.0 h, 5.2 h, 5.3 h, 5.5 h, 5.8 h or 6 h.

[0030] Preferably, the sintering process includes: firstly heating the temperature to a first sintering temperature at a first heating rate for a first sintering heat preservation, and then heating the temperature to a second sintering temperature at a second heating rate for a second sintering heat preservation.

[0031] Preferably, the first heating rate is 8°C / min to 15°C / min, for example, it can be 8°C / min, 8.8°C / min, 9.6°C / min, 10.4°C / min, 11.2°C / min, 11.9°C / min, 12.7°C / min, 13.5°C / min, 14.3°C / min or 15°C / min, etc.

[0032] The present invention needs to set the first heating rate faster to achieve rapid heating so that the B on the surface quickly enters a high-temperature molten state. When the heating rate of the first heating is too slow, the reaction of B is slower than the growth of the LFP particles, which is not conducive to the formation of a BC network. When the heating rate of the first heating is too fast, B melts unevenly, resulting in accumulation and agglomeration, which is not conducive to dispersed and uniform coating.

[0033] Preferably, the first sintering temperature is 500°C to 600°C, for example, it may be 500°C, 510°C, 520°C, 530°C, 545°C, 550°C, 560°C, 575°C, 580°C or 600°C.

[0034] Preferably, the first sintering and heat-keeping time is 1.5 h to 2.5 h, for example, it can be 1.5 h, 1.62 h, 1.73 h, 1.84 h, 1.95 h, 2.06 h, 2.17 h, 2.28 h, 2.39 h or 2.5 h.

[0035] Preferably, the second heating rate is 1°C / min to 5°C / min, for example, it can be 1°C / min, 1.5°C / min, 1.9°C / min, 2.4°C / min, 2.8°C / min, 3.3°C / min, 3.7°C / min, 4.2°C / min, 4.6°C / min or 5°C / min, etc.

[0036] The present invention preferably has the second heating rate lower than the first heating rate, because the temperature has reached 500°C to 600°C or above, and the use of a lower heating rate has the effect of making the crystal nucleus growth more stable and the particle morphology more rounded.

[0037] Preferably, the second sintering temperature is 650°C to 750°C, for example, it may be 650°C, 662°C, 673°C, 684°C, 695°C, 706°C, 717°C, 728°C, 739°C or 750°C.

[0038] Preferably, the second sintering and heat-keeping time is 3 h to 6 h, for example, it can be 3 h, 3.4 h, 3.7 h, 4 h, 4.4 h, 4.7 h, 5 h, 5.4 h, 5.7 h or 6 h.

[0039] Preferably, the preparation of the phosphate-based precursor material comprises: mixing raw materials of the phosphate-based precursor material, and performing ball milling, drying and calcining.

[0040] Preferably, the raw materials of the phosphate-based precursor material include a lithium source, an iron source, a phosphorus source and a carbon source.

[0041] Preferably, the lithium source includes any one of lithium hydroxide, lithium carbonate, lithium sulfate or lithium acetate, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of lithium hydroxide and lithium carbonate, a combination of lithium hydroxide and lithium sulfate, a combination of lithium sulfate and lithium carbonate, and a combination of lithium acetate and lithium carbonate.

[0042] Preferably, the phosphorus source comprises any one of diammonium phosphate, diammonium hydrogen phosphate or phytic acid, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of diammonium phosphate and diammonium hydrogen phosphate, a combination of phytic acid and diammonium hydrogen phosphate, and a combination of diammonium phosphate and phytic acid.

[0043] Preferably, the iron source comprises any one of ferrous phosphate, ferrous sulfate or ferrous oxalate, or a combination of at least two thereof, wherein typical but non-limiting combinations are a combination of ferrous phosphate and ferrous sulfate, a combination of ferrous oxalate and ferrous sulfate, and a combination of ferrous phosphate and ferrous oxalate.

[0044] Preferably, the amount of carbon source added to the raw material of the phosphate-based precursor material is 5wt% to 10wt%, for example, it can be 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt% or 10wt%, etc.

[0045] Preferably, the carbon source in the raw material of the phosphate-based precursor material is any one of glucose, sucrose, citric acid, ethylenediaminetetraacetic acid, polyethylene glycol or graphene, or a combination of at least two of them, wherein typical but non-limiting combinations are a combination of glucose and sucrose, a combination of citric acid and sucrose, a combination of glucose and citric acid, a combination of ethylenediaminetetraacetic acid and graphene, a combination of glucose and ethylenediaminetetraacetic acid, and a combination of polyethylene glycol and ethylenediaminetetraacetic acid.

[0046] Preferably, the ratio of lithium source, iron source and phosphorus source in the raw material of the phosphate precursor material satisfies the molar ratio Li:Fe:P=(1.0-1.5):(0.9-1.1):1, wherein the proportion of Li can be, for example, 1.0, 1.06, 1.12, 1.17, 1.23, 1.28, 1.34, 1.39, 1.45 or 1.5, etc.; the proportion of Fe can be, for example, 0.9, 0.93, 0.95, 0.97, 0.99, 1.02, 1.04, 1.06, 1.08 or 1.1, etc.

[0047] Preferably, the roasting process includes: heating to the roasting temperature and keeping the temperature.

[0048] Preferably, the heating rate of the calcination is 1°C / min to 5°C / min, for example, it can be 1°C / min, 1.5°C / min, 1.9°C / min, 2.4°C / min, 2.8°C / min, 3.3°C / min, 3.7°C / min, 4.2°C / min, 4.6°C / min or 5°C / min, etc.

[0049] Preferably, the calcination temperature is 500°C to 700°C, for example, it may be 500°C, 520°C, 545°C, 565°C, 585°C, 610°C, 635°C, 655°C, 675°C or 700°C.

[0050] Preferably, the insulation time during the roasting is 4 h to 7 h, for example, it can be 4 h, 4.2 h, 4.3 h, 4.4 h, 4.5 h, 4.8 h, 5.0 h, 5.2 h, 5.3 h, 5.5 h, 5.8 h, 6 h, 6.5 h or 7 h.

[0051] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0052] The raw materials of the phosphate precursor material are mixed, ball-milled and dried, and then heated to a calcination temperature of 500°C to 700°C at a heating rate of 1°C / min to 5°C / min and kept warm for 4h to 7h to obtain a phosphate precursor material; wherein the ratio of the lithium source, the iron source and the phosphorus source satisfies the molar ratio of Li:Fe:P=(1.0 to 1.5):(0.9 to 1.1):1, and the amount of the carbon source added is 5wt% to 10wt%, to obtain a phosphate positive electrode precursor material with a carbon coating layer;

[0053] Then mix the phosphate precursor material, the boron source and the carbon source, and take the total amount of raw materials to form a high-density phosphate positive electrode material as the basis, the boron source added in an amount of 500ppm to 2500ppm, the carbon source added in an amount of 5wt% to 10wt%, and perform ball milling at 450rpm to 470rpm for 4h to 6h, then heat it to a first sintering temperature of 500℃ to 600℃ at a first heating rate of 8℃ / min to 15℃ / min, carry out a first sintering and heat preservation for 1.5h to 2.5h, and then heat it to a second sintering temperature of 650℃ to 750℃ at a second heating rate of 1℃ / min to 5℃ / min, carry out a second sintering and heat preservation for 3h to 6h, to obtain a high-density phosphate positive electrode material.

[0054] In a third aspect, the present invention provides a lithium-ion battery positive electrode, which includes the high-density phosphate-based positive electrode material described in the first aspect, and / or the high-density phosphate-based positive electrode material prepared by the preparation method of the high-density phosphate-based positive electrode material described in the second aspect.

[0055] The lithium-ion battery positive electrode provided in the third aspect of the present invention has an excellent compaction density and can prevent the electrolyte from directly contacting the positive electrode material and slowly releasing the capacity, and has broad application prospects because it adopts the high-compacted phosphate positive electrode material described in the first aspect and / or the high-compacted phosphate positive electrode material prepared by the preparation method of the high-compacted phosphate positive electrode material described in the second aspect.

[0056] The present invention has no special restrictions on the specific structure and other materials in the above-mentioned lithium ion battery positive electrode. Any structure and material that can be used for the positive electrode of the lithium ion battery known to those skilled in the art can be adopted, and can also be adjusted according to actual conditions. For example, the positive electrode current collector is aluminum, etc. The conductive agent in the slurry preparation process can be one or more of carbon nanotubes, graphene, carbon black and carbon fibers, preferably one or more of carbon nanotubes, graphene and carbon black; the binder can be one or more of polyvinylidene fluoride PVDF, sodium carboxymethyl cellulose CMC, styrene butadiene rubber SBR, acrylonitrile multipolymer LA and polyacrylic acid PAA, preferably one or more of polyvinylidene fluoride PVDF, sodium carboxymethyl cellulose CMC and styrene butadiene rubber SBR; the solvent is one or more of N-methylpyrrolidone NMP, deionized water, acetone and dimethylacetamide DMAC, preferably one or more of N-methylpyrrolidone NMP, acetone and dimethylacetamide DMAC. The specific amount is selected according to the preparation of positive electrode sheets and lithium ion batteries in the art, and the amount added is not limited.

[0057] Compared with the prior art, the present invention has at least the following beneficial effects:

[0058] (1) The high-density phosphate-based cathode material provided by the present invention can improve the particle morphology and particle roundness, and can obtain a phosphate-based cathode material with a proper particle size mixture, thereby improving the compaction density of the phosphate-based cathode material;

[0059] (2) The B introduced into the high-density phosphate-based positive electrode material provided by the present invention can form a dense film on the surface of the positive electrode material, slowly release the capacity, and form a climbing effect during the cycle process, thereby improving the application prospects of the positive electrode material;

[0060] (3) The preparation method of the high-density phosphate-based positive electrode material provided by the present invention uses a two-stage sintering process, which first allows the surface B to quickly enter a high-temperature molten state, and then effectively coats B and C on the finished phosphate-based positive electrode material to achieve the purpose of regulating the morphology. BRIEF DESCRIPTION OF THE DRAWINGS

[0061] Figure 1 This is a SEM image of the high-density phosphate-based positive electrode material prepared in Example 1 of the present invention.

[0062] Figure 2 It is a SEM picture of the phosphate-based positive electrode material prepared in Comparative Example 1 of the present invention.

[0063] Figure 3 This is a graph showing the change in discharge capacity of the phosphate-based positive electrode materials prepared in Comparative Example 1, Example 1, Example 4 and Example 5 of the present invention in lithium-ion batteries as a function of the number of cycles.

[0064] Figure 4 It is the XPS graph of the B element in the phosphate-based positive electrode material prepared in Example 1 of the present invention and the XPS graph of the P element in the phosphate-based positive electrode material in Comparative Example 1. DETAILED DESCRIPTION

[0065] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0066] It should be understood that, in the description of the present invention, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, a feature defined as "first", "second", etc. may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "plurality" means two or more.

[0067] Example 1

[0068] This embodiment provides a method for preparing a high-density phosphate-based positive electrode material, the preparation method comprising the following steps:

[0069] (1) Mix the raw materials of the phosphate precursor material LiFePO4, namely, 3.52 g of lithium hydroxide, 20.43 g of ferrous sulfate heptahydrate, 16.90 g of ammonium dihydrogen phosphate, and 1.2 g of glucose, and add them into a 500 mL ball mill. Add anhydrous ethanol and ball milling beads, mix and ball mill on a planetary ball mill for 6 h, and then dry, grind and sieve.

[0070] (2) Then, the temperature is raised to 600° C. at a heating rate of 3° C. / min and kept at this temperature for 4 h to obtain a phosphate-based precursor material.

[0071] (3) Based on the total amount of raw materials for forming a high-density phosphate-based positive electrode material, 24 g of a mixed phosphate-based precursor material, 2000 ppm of the boron source (boron oxide), and 10 wt % of the carbon source (glucose) were added. The above raw materials were added to a ball mill, ball milling beads were added, and the mixture was milled at 450 rpm in a planetary ball mill for 4.5 h.

[0072] (4) Then, the temperature is increased to a first sintering temperature of 600°C at a first heating rate of 12°C / min and the first sintering is carried out at a heat preservation temperature of 2.0 h. Then, the temperature is increased to a second sintering temperature of 700°C at a second heating rate of 5°C / min and the second sintering is carried out at a heat preservation temperature of 6 h. After cooling and grinding, a high-density phosphate-based positive electrode material is obtained.

[0073] The high-density phosphate-based positive electrode material includes a phosphate-based inner core and a BC composite coating layer coated on the surface of the phosphate-based inner core, wherein the BC composite coating layer includes BC3, borate and amorphous carbon.

[0074] Example 2

[0075] This embodiment provides a method for preparing a high-density phosphate-based positive electrode material, the preparation method comprising the following steps:

[0076] (1) Mixed phosphate precursor material LiFe 0.6 Mn 0.4 The raw materials of PO4, 6.71 g lithium sulfate, 10.53 g ferrous oxalate, 8.73 g diammonium phosphate, 1.2 g sucrose, and 14.03 g manganese nitrate, were added to a 500 mL ball mill jar, anhydrous ethanol and ball milling beads were added, and the mixture was mixed and ball milled on a planetary ball mill for 4 hours, and then dried, ground and sieved.

[0077] (2) Then, the temperature is raised to 500° C. at a heating rate of 1° C. / min and kept at this temperature for 7 h to obtain a phosphate-based precursor material.

[0078] (3) Based on the total amount of raw materials for forming a high-density phosphate-based positive electrode material, 22 g of a mixed phosphate-based precursor material, 2000 ppm of the boron source (boron oxide), and 5 wt % of the carbon source (glucose) were added, and the above raw materials were added to a ball milling jar, ball milling beads were added, and ball milling was performed in a planetary ball mill at 455 rpm for 4.5 h;

[0079] (4) Then, the temperature was increased to a first sintering temperature of 500°C at a first heating rate of 15°C / min and the first sintering was carried out at a heat preservation temperature of 2.5 hours. Then, the temperature was increased to a second sintering temperature of 650°C at a second heating rate of 1°C / min and the second sintering was carried out at a heat preservation temperature of 3 hours. After cooling and grinding, a high-density phosphate-based positive electrode material was obtained.

[0080] The high-density phosphate-based positive electrode material includes a phosphate-based inner core and a BC composite coating layer coated on the surface of the phosphate-based inner core, wherein the BC composite coating layer includes BC3, borate and amorphous carbon.

[0081] Example 3

[0082] This embodiment provides a method for preparing a high-density phosphate-based positive electrode material, the preparation method comprising the following steps:

[0083] (1) Mix the raw materials of the phosphate precursor material LiFePO4, namely, lithium acetate 12.71 g, iron phosphate 26.28 g, phytic acid 1.01 g, and ethylenediaminetetraacetic acid 1.2 g, and add them into a 500 mL ball mill, add anhydrous ethanol and ball milling beads, mix and ball mill on a planetary ball mill for 5 h, and then dry, grind and sieve.

[0084] (2) Then, the temperature is raised to 600° C. at a heating rate of 3° C. / min and kept at this temperature for 5 h to obtain a phosphate-based precursor material.

[0085] (3) Based on the total amount of raw materials for forming a high-density phosphate-based positive electrode material, 22 g of a mixed phosphate-based precursor material, 2000 ppm of the boron source (boron oxide), and 5 wt % of the carbon source (glucose) were added, and the above raw materials were added to a ball milling jar, ball milling beads were added, and ball milling was performed in a planetary ball mill at 455 rpm for 4.5 h;

[0086] (4) Then, the temperature is increased to a first sintering temperature of 600°C at a first heating rate of 8°C / min and the first sintering is carried out at a heat preservation temperature of 1.5 h. Then, the temperature is increased to a second sintering temperature of 750°C at a second heating rate of 5°C / min and the second sintering is carried out at a heat preservation temperature of 6 h. After cooling and grinding, a high-density phosphate-based positive electrode material is obtained.

[0087] The high-density phosphate-based positive electrode material includes a phosphate-based inner core and a BC composite coating layer coated on the surface of the phosphate-based inner core, wherein the BC composite coating layer includes BC3, borate and amorphous carbon.

[0088] Example 4

[0089] This embodiment provides a method for preparing a high-density phosphate-based positive electrode material. The preparation method is the same as that of Example 1 except that the amount of boron source added is 500 ppm, and will not be described in detail here.

[0090] Example 5

[0091] This embodiment provides a method for preparing a high-density phosphate-based positive electrode material. The preparation method is the same as that of Example 1 except that the amount of boron source added is 3000 ppm, and will not be described in detail here.

[0092] Example 6

[0093] This embodiment provides a method for preparing a high-density phosphate-based positive electrode material. The preparation method is the same as that of Embodiment 1 except that the temperature is increased to a first sintering temperature of 600° C. at a first heating rate of 6° C. / min in step (4), and will not be described in detail here.

[0094] Example 7

[0095] This embodiment provides a method for preparing a high-density phosphate-based positive electrode material. The preparation method is the same as that of Embodiment 1 except that the temperature is increased to a first sintering temperature of 600° C. at a first heating rate of 18° C. / min in step (4), and will not be described in detail here.

[0096] Example 8

[0097] This embodiment provides a method for preparing a high-density phosphate-based positive electrode material. The preparation method is the same as that of Embodiment 1 except that boron oxide is replaced by boron element, and will not be described in detail here.

[0098] Example 9

[0099] This embodiment provides a method for preparing a high-density phosphate-based positive electrode material. The preparation method is the same as that of Embodiment 1 except that boron oxide is replaced by boron carbide, and will not be described in detail here.

[0100] Comparative Example 1

[0101] This comparative example provides a method for preparing a phosphate-based positive electrode material. The preparation method is the same as Example 1 except that boron oxide is not added in step (3), and will not be described in detail here.

[0102] Comparative Example 2

[0103] This comparative example provides a method for preparing a phosphate-based positive electrode material. The preparation method is the same as Example 1 except that no carbon source (glucose) is added in step (3), and will not be described in detail here.

[0104] Comparative Example 3

[0105] This comparative example provides a method for preparing a phosphate-based positive electrode material. The preparation method is the same as Example 1 except that boron oxide is replaced by silicon oxide in step (3), and the details are not repeated here.

[0106] Comparative Example 4

[0107] This comparative example provides a method for preparing a phosphate-based positive electrode material. The preparation method is the same as Example 1 except that the boron oxide in step (3) is added to step (1) and step (3) is not performed, and the rest is not repeated here.

[0108] Test method: In order to facilitate comparative experiments, the performance of the lithium-ion positive electrode materials obtained in the above embodiments and comparative examples was tested using the following lithium-ion battery preparation method, which is:

[0109] The above lithium iron phosphate composite material was mixed with polyvinylidene fluoride (PVDF) and CNTs (carbon nanotubes) in a mass ratio of 96:3:1, N-methylpyrrolidone (NMP) was used as a solvent to prepare a positive electrode sheet, a metal lithium sheet was used as a counter electrode, a Celgard2400 porous polypropylene film (PP) was used as a separator, the electrolyte was a 1 mol / L lithium hexafluorophosphate (LiPF6) solution, and the solvent was a mixed solution of ethylene carbonate (EC): ethyl carbonate (DMC) in a volume ratio of 1:1. R2032 button batteries were prepared according to a certain assembly process. After completion, they were left to stand for 3 hours to allow the electrolyte and electrode materials to be fully infiltrated.

[0110] Electrochemical performance test: At room temperature (25℃±1), constant current and constant voltage charge and discharge experiments were carried out on Li / Li+ under 1C conditions, and the cycles were 150 cycles.

[0111] Particle size testing method: A laser particle size analyzer was used to test the particle size D50 of the materials obtained in each embodiment and comparative example.

[0112] Compacted density test method: A compacted density meter was used to test the compacted density of the materials obtained in each embodiment and comparative example.

[0113] B content testing method: ICP was used to test the B content of the materials obtained in each embodiment and comparative example.

[0114] C content testing method: The C content of the materials obtained in each embodiment and comparative example was tested by a carbon-sulfur analyzer.

[0115] Depend on Figure 1It can be seen that the particles of the sample modified by coating in Example 1 are relatively round and have a certain particle size distribution, which increases the compaction density. Figure 2 It can be seen that the particles of the sample without coating modification in Comparative Example 1 are irregular, the particles are overall small, and the particle size distribution is uneven, resulting in a low compaction density. Figure 3 It can be seen that after the surface is coated with the BC layer, the discharge capacity retention rate of the sample 1P cycle has a climbing phenomenon, and the capacity is slowly released, which is beneficial to the application in the energy storage direction. According to Example 1 and the XPS B1s fine spectrum, ( Figure 4 ), there are various bond states of B on the surface of the B-doped sample of Example 1, such as BC bond and BO bond. According to the peak separation results, its main components are BC3 and borates (Li3BO3, LiFeBO3, Li2B4O7). BC3 can change the valence band structure of carbon-based materials and increase the state density near the Fermi level, thereby improving the electronic conductivity of LFP; borates containing silver borate ions (any one or a combination of at least two of Li2B4O7, Li3BO3, Fe3(BO3)4 or LiFeBO3) have the effect of slowly releasing capacity, which is consistent with the electrochemical performance results. The test results of the above embodiments and comparative examples are shown in Tables 1 and 2.

[0116] Table 1

[0117]

[0118] Table 2

[0119]

[0120] In Table 1, “ / ” indicates that there is no related substance.

[0121] From Tables 1 and 2, we can see the following points:

[0122] (1) Based on Examples 1 to 3, it can be seen that the high-density phosphate-based positive electrode material and the preparation method thereof provided by the present invention can obtain a D50 of less than or equal to 0.988 μm and a compaction density of 2.630 g / cm 3 It is a positive electrode material with excellent long-term cycle stability. After it is used as a positive electrode material to make a battery, the 1C first discharge capacity is above 134.8mAh / g, the 1C first charge capacity is above 140.9mAh / g, and the 150-week capacity retention rate is above 102.63%, with basically no decline, and has broad application prospects;

[0123] (2) Combining Example 1 and Examples 4 to 5, it can be seen that the amount of boron source added in Example 1 is 2000ppm, compared with 500ppm in Example 4 and 3000ppm in Example 5. In Example 1, the 1C first discharge capacity is 134.8mAh / g, the 1C first charge capacity is 141.6mAh / g, and the capacity retention rate for 150 weeks is 103.37%, while the capacity retention rates for 150 weeks in Examples 4 to 5 are 100.91% and 102.59%, respectively. This shows that the present invention can be more conducive to improving the cycle performance of the battery by preferably controlling the amount of boron source added within a reasonable range;

[0124] (3) It can be seen from the combination of Example 1 and Examples 6-7 that in step (4) of Example 1, the first heating rate is 12°C / min to the first sintering temperature of 600°C. Compared with the first heating rates of 6°C / min and 18°C / min in Examples 6-7, respectively, the compacted density of the sample obtained in Example 1 is 2.630 g / cm 3 , the 1C first discharge capacity is 134.8 mAh / g, the 1C first charge capacity is 141.6 mAh / g, the capacity retention rate for 150 weeks is 103.37%, and the compaction density of the samples prepared in Examples 6 to 7 is 2.518 g / cm 3 and 2.543 g / cm 3 , and the capacity retention rates after 150 weeks are only 99.78% and 99.48%, respectively. This shows that the present invention can be more conducive to improving the compaction density of the positive electrode material and improving the cycle performance of the battery by preferably controlling the heating rate of the first sintering within a reasonable range;

[0125] (4) In step (3) of comparative example 1, no boron oxide was added, and the compacted density was only 2.419 g / cm 3 , the capacity retention rate after 150 weeks is only 93.75%. In comparative example 4, the boron oxide in step (3) is added to step (1), and step (3) is not performed. The capacity retention rate after 150 weeks is only 93.52%. This shows that the present invention can increase the compaction density of the phosphate-based positive electrode material and significantly improve the cycle performance of the battery by adding a boron source to the sintered phosphate-based positive electrode material.

[0126] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A high-density phosphate-based cathode material, characterized in that: The phosphate-based positive electrode material comprises a phosphate-based core and a BC composite coating layer coated on the surface of the phosphate-based core, wherein the BC composite coating layer comprises BC3, borate and amorphous carbon; the borate has a general formula of M x B y O z , wherein M includes Li and / or Fe, x is 1-3, y is 1-4, and z is 3-7.

2. The high-density phosphate-based cathode material according to claim 1, characterized in that: The borate includes any one or a combination of at least two of Li2B4O7, Li3BO3, Fe3(BO3)4 or LiFeBO3; Preferably, the phosphate-based core includes lithium iron phosphate and / or lithium iron manganese phosphate; Preferably, the particle size D50 of the phosphate-based positive electrode material is 0.8 μm to 1.1 μm; Preferably, the thickness of the BC composite coating layer is 4 nm to 7 nm.

3. The high-density phosphate-based cathode material according to claim 1 or 2, characterized in that: The B content in the high-density phosphate-based positive electrode material is 500ppm to 2500ppm; Preferably, the C content in the high-density phosphate-based positive electrode material is 1.2 wt% to 1.7 wt%.

4. A method for preparing a high-density phosphate-based cathode material according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: A phosphate-based precursor material, a boron source and a carbon source are mixed, and ball milling and sintering are performed in sequence to obtain a high-density phosphate-based positive electrode material.

5. The preparation method according to claim 4, characterized in that: The boron source includes boron oxide and / or boric acid; Preferably, the carbon source comprises any one of glucose, sucrose, citric acid, ethylenediaminetetraacetic acid, polyethylene glycol or graphene, or a combination of at least two thereof; Preferably, based on the total amount of raw materials for forming the high-density phosphate-based positive electrode material, the amount of boron source added is 500ppm to 2500ppm; Preferably, based on the total amount of raw materials for forming the high-density phosphate-based positive electrode material, the amount of the carbon source added is 5 wt % to 10 wt %.

6. The preparation method according to claim 4 or 5, characterized in that: The rotation speed of the ball mill is 450 rpm to 470 rpm; Preferably, the ball milling time is 4 h to 6 h.

7. The preparation method according to any one of claims 4 to 6, characterized in that: The sintering process includes: firstly heating the temperature to a first sintering temperature at a first heating rate for a first sintering heat preservation, and then heating the temperature to a second sintering temperature at a second heating rate for a second sintering heat preservation; Preferably, the first heating rate is 8°C / min to 15°C / min; Preferably, the first sintering temperature is 500° C. to 600° C.; Preferably, the first sintering and heat preservation time is 1.5h to 2.5h; Preferably, the second heating rate is 1°C / min to 5°C / min; Preferably, the second sintering temperature is 650°C to 750°C; Preferably, the second sintering and heat-keeping time is 3 hours to 6 hours.

8. The preparation method according to any one of claims 4 to 7, characterized in that: The preparation of the phosphate precursor material comprises: mixing the raw materials of the phosphate precursor material, and performing ball milling, drying and roasting; Preferably, the raw materials of the phosphate-based precursor material include a lithium source, an iron source, a phosphorus source and a carbon source; Preferably, the amount of carbon source added to the raw material of the phosphate-based precursor material is 5wt% to 10wt%; Preferably, the carbon source in the raw material of the phosphate-based precursor material is any one of glucose, sucrose, citric acid, ethylenediaminetetraacetic acid, polyethylene glycol or graphene, or a combination of at least two thereof; Preferably, the ratio of the lithium source, the iron source and the phosphorus source in the raw material of the phosphate-based precursor material satisfies the molar ratio of Li:Fe:P=(1.0-1.5):(0.9-1.1):

1.

9. The preparation method according to any one of claims 4 to 8, characterized in that: The roasting process includes: heating to the roasting temperature and keeping the temperature; Preferably, the heating rate of the calcination is 1°C / min to 5°C / min; Preferably, the calcination temperature is 500°C to 700°C; Preferably, the heat preservation time during the roasting is 4h to 7h.

10. A positive electrode for a lithium ion battery, characterized in that: The lithium ion positive electrode comprises the high-density phosphate positive electrode material described in any one of claims 1 to 3, and / or the high-density phosphate positive electrode material prepared by the preparation method of the high-density phosphate positive electrode material described in any one of claims 4 to 9.

Citation Information

Cited By

  • Lithium iron phosphate positive electrode material with high cycle stability and preparation method of lithium iron phosphate positive electrode material

    CN120998972A